A Review of Dr. Jamil Jalibi’s Concept of National Unity through Pakistani Culture (The Problem of Formation of National Culture) - Shad, Elizabeth; Sarfraz, Sarah (sourcecoder, 2022)
Jamil Jalibi is a famous scholar, researcher, writer and former vice chancellor of the University of Karachi. He wrote over 40 books on criticism, research and culture. He had a zeal for creating and was prolific in his literary output but he was always shy of conversation, avoided interviews, discussions, and gatherings. He prefers reading from the prepared text even in limited literary gatherings. Besides his monumental work of the four-volume history of Urdu literature, he authored several other books which included; Qadeem Urdu ki Lughat, Pakistani Culture, Tanqeed aur Tajarba, Nai Tanqeed, Adab, Culture aur Masail, Ma’asir Adab, Eliot kay Mazameen, Arasto say Eliot tak (translation), Janvaristan (translation), Masnawi Kadam Rao Padam Rao (edited). In recognition of his services the government bestowed on him the Sitara-i-Imtiaz, Hilal-e-Imtiaz and Nishan-e-Imtiaz.This article is an effort to give a scholarly review of his book Pakistani Culture. It highlights the importance of culture, its values and civilization. It gives a deep insight of Pakistani Culture and its impact on the people.